The experience of creating and using seven soil databases in the Soil-Geoeocophysics Laboratory - Laktionova, T.M. (AgroChemistry and Soil Science, 2018)
The purpose of the review article is to highlight the peculiarities of the development of the direction for creating sets and bases of data for solving scientific tasks of the Laboratory. In a chronological sequence, there is a description of 7 databases created by the Laboratory staff and the results of application of the accumulated information are briefly shown. The history of the origin and development of informational subjects began with the first attempt to accumulate in the reference-book the results of their own expeditionary research regarding the hydrophysical properties of soils. The continuation was the creation of a modern complex soil profile database for geo-positioned data and the participation of the Laboratory in large international databases in creative collaboration with international teams of scientists. The methodology for creating databases in the laboratory has always been based on the principle of preserving all available information relating to field surveys and soil cover studies in Ukraine. There were collected both direct soil parameters and related physical data characterizing the special features of formation and explain the variability of soil properties. The dominant methodological approaches are to provide multifunctionality and associativity of databases. This principle has allowed widely use of data sets in research and targeted developments in a large thematic circle, as well as the delegation of data sets to international geographic information systems. In order to process the accumulated data, there were gradually developed special methodological approaches and algorithms for cartographic and analytical assessment of the state and quality of soils and prediction of their changes using pedotransfer rules. It was developed own theory of soil-technological regionalization of arable land of Ukraine, illustrated by a set of cartographic materials. By elaboration of a large number of soil physical parameters, an algorithm for determining of soil physical quality as an integral part of an objective assessment of soil is created. All databases created by the Laboratory are considered as contributing to the currently developed Soil Information System of Ukraine, which should be the methodological basis for the future activities of the Ukrainian Soil Information Center.